Cholesterol–based Bisamides on Biphenyl Backbone: A Case of Selective Visual Sensing of F− and H2PO4− through Breaking and Making of Gels. Issue 13 (19th August 2016) - Ghosh, Kumaresh; Panja, Santanu
Abstract: Cholesterol linked bisamides1–3 on biphenyl spacers have been designed and synthesized. Compound1 forms gel in CHCl3 – n‐hexane (1:6, v/v) solvent and the gel is selectively collapsed into sol in presence of F − with a color change from yellowish white to greenish yellow. Presence of pyridinium amides in2 and3 showed different gelation behaviours. While the chloride salt2 displayed gelation in CHCl3 in presence of H2 PO4 −, compound3 formed gel in DMSO: H2 O (1:2, v/v) without having any assistance of externally added anion. The gel derived from3 underwent rapid gel to sol transition in presence of H2 PO4 − and F − anions and validated their visual sensing. Abstract : We report the design, synthesis and recognition behavior of some cholesterol linked bisamides on biphenyl backbone in sol gel medium. Bisamides either form gel in the presence of H2 PO4 − or gels derived from them are selectively collapsed into sol in the presence of H2 PO4 − and F − anions and validate their visual sensing.